2003
DOI: 10.5424/sjar/2003014-45
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some processing tomato lines with resistance to Tomato spotted wilt virus for agricultural and processing characters

Abstract: Nowadays, Tomato spotted wilt virus (TSWV) is one of the most limiting factors for tomato culture in Spain. Some breeding programs have been recently developed to obtain cultivars with resistance to TSWV. The evaluation of six lines of processing tomato obtained from one of these breeding programs and carrying the Sw-5 gene that confers resistance to TSWV, has shown that all these lines have both agronomic (yield, vigor, etc.) and quality characters better or similar to those of control cultivars. The lines te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The economic impact of TSWV is great, due to its wide geographical distribution and to its broad host range. Crops in which important losses due to TSWV have been reported are tomato, pepper, lettuce, eggplant, papaya, French beans, celery and ornamental plants (Gragera et al 2003;Rosello et al 1996). Infection rates of 30-100% lead to major losses in commercial vegetable crops.…”
Section: Discussionmentioning
confidence: 99%
“…The economic impact of TSWV is great, due to its wide geographical distribution and to its broad host range. Crops in which important losses due to TSWV have been reported are tomato, pepper, lettuce, eggplant, papaya, French beans, celery and ornamental plants (Gragera et al 2003;Rosello et al 1996). Infection rates of 30-100% lead to major losses in commercial vegetable crops.…”
Section: Discussionmentioning
confidence: 99%
“…It is requested that all resistant or tolerant tomato cultivars will have high yielding ability and desirable quality characters. Gragera et al (2003) found that six tomato lines carrying the Sw-5 gene (originating from one of the previous breeding programmes) had both agronomic and quality characters better or as good as control cultivars. Such lines or cultivars can be very useful for the development of hybrids that would express heterosis and stability in different environmental conditions, particularly in regions where TSWV is an endemic disease.…”
Section: Tswv Breeding Strategiesmentioning
confidence: 99%